Analisis Kesehatan Koperasi Syariah dalam Upaya Meningkatkan Kinerja dan Pelayanan - Antin Okfitasari; Agus Suyatno (ITB AAS INDONESIA Surakarta, 2018)
The purpose of research is to analyze the financial health of Savings and Loans Cooperative and Sharia (KSPPS) BMT Mitra Mandiri Wonogiri, Central Java. This research method is quantitative descriptive approach, with sample of KSPPS financial reports from year 2013 until 2016. Permenkop-UKM number 7 / Per / Dep.6 / IV / 2016, is used as a data analysis tool, which includes capital aspect, quality aspect of productive assets, efficiency aspect, liquidity aspect, and independence aspect and growth aspect. The result based on each health assessment indicator, all indicators indicate healthy category except capital aspect. The financial health assessment of KSPPS BMT Mitra Mandiri from 2013 to 2016 in aggregate and per year show healthy category. Saran sitasi: Okfitasari, A., & Suyatno, A. (2018). Analisis Kesehatan Koperasi Syariah dalam Upaya Meningkatkan Kinerja dan Pelayanan. Jurnal Ilmiah Ekonomi Islam, 4(2), 103-115. doi:http://dx.doi.org/10.29040/jiei.v4i2.260